Peramalan Jumlah Pengunjung Objek Wisata Waterboom Kota Sawahlunto Tahun 2019 Menggunakan Metode SARIMA - ulfah hanum; dewi murni (Journal of Mathematics UNP, 2019)
Abstract–The visitors of tourist attraction will change and tend to be inconsistent over the tim, one of them is Waterboom which is located in Sawahlunto. This tourist object lacks of public facilities when it shows the increasing number of the visitors. Therefore, it is needed to make a prediction as the base in decision making. This research to make a model ARIMA and to get the prediction’s result of the total number of the Waterboom’s visitors in 2019. The data used are the number of the Waterboom’s visitors from January, 2014 up to December, 2018. Data analysis using the Seasonal Autoregressive Integrated Moving Average (SARIMA). This method consists of identification model, falsification stage and parameter testing, diagnostic stage, and forecasting stage. The analysis’s result in this study gets the best model for predicting data  of the total number of the visitors of Waterboom in Sawahlunto that is ARIMA(1,1,1)(0,1,0)12, and this model is used to make a prediction in the next 12 periods.Keywords–The Number of visitors, SARIMA’s Model, Forecasting